Optimising the visibility of graphene and graphene oxide on gold with multilayer heterostructures. (9th May 2018) - Velický, Matěj; Hendren, William R; Donnelly, Gavin E; Katzen, Joel M; Bowman, Robert M; Huang, Fumin
Abstract: Metals have been increasingly used as substrates in devices based on two-dimensional (2D) materials. However, the high reflectivity of bulk metals results in low optical contrast (<3%) and therefore poor visibility of transparent mono- and few-layer 2D materials on these surfaces. Here we demonstrate that by engineering the complex reflectivity of a purpose-designed multilayer heterostructure composed of thin Au films (2–8 nm) on SiO2 /Si substrate, the optical contrast of graphene and graphene oxide (GO) can be significantly enhanced in comparison to bulk Au, up to about 3 and 5 times, respectively. In particular, we achieved ∼17% optical contrast for monolayer GO, which is even 2 times higher than that on bare SiO2 /Si substrate. The experimental results are in good agreement with theoretical simulations. This concept is demonstrated for Au, but the methodology is applicable to other metals and can be adopted to design a variety of high-contrast metallic substrates. This will facilitate research and applications of 2D materials in areas such as plasmonics, photonics, catalysis and sensors.